STRATEGI GREETER DALAM MENINGKATKAN PELAYANAN PRIMA UNTUK MEMINIMALISIR KOMPLAIN DI ABHAYAGIRI RESTAURANT YOGYAKARTA - Setyoatmodjo, Kukuh; Rusdiana, Restu Putri (AKPARDA, 2023)
Abhayagiri Restaurant is well known both in the city of Yogyakarta and outside the city of Yogyakarta, thus many guests come to Abhayagiri Restaurant. To support smooth operations, Abhayagiri Restaurant has its own standard procedures to improve excellent service to guests who come to the restaurant. At Abhayagiri Restaurant, which is usually a source of guest dissatisfaction, it is generally caused by less than optimal service from a greeter because the number of guests who come is not proportional to the number of existing waiter/waitress staff, so in this case the greeter cannot carry out all the sequence of service procedures, because the greeter also doubles as a waiter/waitress. The importance of the service of a greeter is to give the guest the first and last impression. If the guest is impressed with the service received, it will create a plus for the restaurant, which will make the guest come back again and increase guest visits. To achieve this, a greeter must know the strategy to improve excellent service. Therefore, the author raised the title